Histomorphologic and Immunohistochemical Characterization of a Cardiac Purkinjeoma in a Bearded Seal (Erignathus barbatus). (31st August 2014) - Krafsur, G.; Ehrhart, E. J.; Ramos-Vara, J.; Mason, G.; Sarren, F.; Adams, B.; Hanns, C.; Spraker, T.; Duncan, C.
Abstract : The most common cardiac tumors of heart muscle are rhabdomyomas, solitary or multiple benign tumors of striated muscle origin. While cardiac rhabdomyomas are well described in human medical literature, limited information depicting the occurrence of cardiac rhabdomyomas in veterinary species exists. A case of multiple firm white nonencapsulated nodules in the heart of a bearded seal is described. Microscopic findings included cytoplasmic vacuolization with formation of spider cells, glycogen vacuoles, and striated myofibrils. These cells expressed immunoreactivity for neuron-specific enolase and protein gene product 9.5, a marker for neuronal tissue and Purkinje fiber cells. Immunoreactivity for protein gene product 9.5 along with other microscopic findings substantiates Purkinje fiber cell origin of the cardiac rhabdomyoma in the bearded seal and use of the term purkinjeoma to describe this lesion.